VALIDITAS MODUL PEMBELAJARAN MENGONSTRUKSI KARYA ILMIAH BERBASIS PROJECT BASED LEARNING SISWA KELAS XI SMA - Saputri, Meliana; Hartati, Yulia Sri; Dwinitia, Suci (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
This study aims to determine the validation of the learning module for constructing scientific papers for class XI SMA based on the assessments of content/material experts, linguists and graphic experts. The research method used is research and development (R&D) with a 4-D (Four-D) model. The 4-D model consists of four stages, namely define, design, develop and disseminate. The instrument used is a validation sheet filled out by experts in their fields to test the feasibility of content, presentation feasibility, project based learning, language feasibility and graphic feasibility. The data analysis technique used is a Likert scale with a scale of 0-10. Based on the results of expert validation, the developed learning module is categorized as valid with a value of 90.86. Keywords: Validity, Module, Constructing Scientific Work